Folliculitis decalvans. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
Folliculitis decalvans can affect both sexes but in males the onset is more precocious starting from adolescence. Folliculitis usually affects the vertex and the occipital area, often recurring in the same areas till to destroy the hair follicles involved and to cause cicatricial alopecia in small multiple foci (1). Bacteriological tests often show Staphylococcus aureus, but its pathogenic role is questionable; it is more likely that an abnormal reaction to this pathogen is involved, as shown by the usefulness of immunosuppressive treatment. Histological examination reveals the presence of neutrophils in and around the hair follicles. There is no elective treatment of folliculitis decalvans: topical and oral antibiotics, topical tacrolimus, topical and intralesional corticosteroids, dapsone, isotretinoin have been used with varying results in different cases (2).